Reported Sildenafil Side Effects in Pediatric Pulmonary Hypertension Patients - Siehr, Stephanie L.; McCarthy, Elisa K.; Ogawa, Michelle T.; Feinstein, Jeffrey A. (Frontiers in Pediatrics, 2015)
Background: Sildenafil, a phosphodiestase type 5 inhibitor, was approved in 2005 for the treatment of pulmonary arterial hypertension (PAH) in adults, and is commonly used off-label for pediatric patients. Little is known, however, about sildenafil’s side effects in this population. Methods: Single institution, longitudinal survey-based study performed in an outpatient pediatric cardiology clinic. Pediatric patients on sildenafil (alone or in combination with other PH therapies) completed questionnaires regarding frequency of vascular, gastrointestinal, neurologic and hematologic side effects. Results: Between January 2011 and May 2014, 66 pediatric patients with PH on sildenafil filled out 214 surveys, 32 patients (96 surveys) on monotherapy, and 43 patients (118 surveys) on sildenafil plus an endothelin receptor antagonist (bosentan or ambrisentan) and/or a prostacyclin (epoprostenol or treprostinil). Overall, 30% of respondents identified at least one side effect. For all patients on sildenafil, incidence of side effects by system was 37% gastrointestinal, 35% vascular and 22% neurologic. For patients on sildenafil monotherapy, incidence of side effects by system was 24% gastrointestinal, 21% vascular and 18% neurologic compared to patients on combination therapy who reported an incidence of 48% gastrointestinal, 45% vascular and 25% neurologic. Conclusion: Incidence of vascular, gastrointestinal and neurologic side effect in pediatric patients on sildenafil therapy for pulmonary arterial hypertension was 30%. Side effects were more common in patients on combination therapy with an endothelin receptor antagonist and/or prostacyclin than in patients on sildenafil monotherapy.